2017
DOI: 10.1155/2017/4763937
|View full text |Cite
|
Sign up to set email alerts
|

Separation Process of Fine Coals by Ultrasonic Vibration Gas-Solid Fluidized Bed

Abstract: Ultrasonic vibration gas-solid fluidized bed was proposed and introduced to separate fine coals (0.5–0.125 mm fraction). Several technological methods such as XRF, XRD, XPS, and EPMA were used to study the composition of heavy products to evaluate the separation effect. Results show that the ultrasonic vibration force field strengthens the particle separation process based on density when the vibration frequency is 35 kHz and the fluidization number is 1.8. The ash difference between the light and heavy produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The experimental results of many researchers showed that superficial air velocity was the major parameter affecting the separation [ [231] , [232] , [233] , [234] , [235] ], followed by vibration (i.e., amplitude [ 230 , 231 , 233 , 234 ] and frequency [ 230 , 231 , [233] , [234] , [235] ]) and other parameters (i.e., feed rate [ 236 ] and separation time [ 230 ]) while bed height did not significantly affect the separation [ 231 , 234 ] (Table S3). Recently, ultrasonic vibration gas-solid fluidized bed was developed to separate coal and high-density impurities like pyrite, quartz, and kaolinite using ultrasonic vibration force field [ 237 ].…”
Section: Dry-type Gravity Separation Technologiesmentioning
confidence: 99%
“…The experimental results of many researchers showed that superficial air velocity was the major parameter affecting the separation [ [231] , [232] , [233] , [234] , [235] ], followed by vibration (i.e., amplitude [ 230 , 231 , 233 , 234 ] and frequency [ 230 , 231 , [233] , [234] , [235] ]) and other parameters (i.e., feed rate [ 236 ] and separation time [ 230 ]) while bed height did not significantly affect the separation [ 231 , 234 ] (Table S3). Recently, ultrasonic vibration gas-solid fluidized bed was developed to separate coal and high-density impurities like pyrite, quartz, and kaolinite using ultrasonic vibration force field [ 237 ].…”
Section: Dry-type Gravity Separation Technologiesmentioning
confidence: 99%